The experiment of faith : Pope Benedict XVI on living the theological virtues in a secular age - Ramage, Matthew J. (The Catholic University of America Press, 2020)
"This book provides an apology for the Christian faith in the face of the particular challenges of postmodern life and thought. The author argues that Christian faith is best seen through the practice of Christian life in all its dimensions, and uses the writings of Benedict XVI to elucidate what this means in terms of the theological virtues of faith, hope, and charity"--